Physical simulation and feasibility evaluation for construction of salt cavern energy storage with recycled light brine under gas blanket. (25th November 2022) - Li, Depeng; Liu, Wei; Li, Xiaoshuang; Tang, Haijun; Xu, Guichun; Jiang, Deyi; Du, Jinwu; Zhang, Xiong; Fan, Jinyang
Abstract: The high cost and serious pollution of salt cavern construction (SCC) with fresh water (FW) under oil blanket (OB) poses a major challenge to the development of salt cavern energy storage, and it is of great significance for clean brine mining and efficient SCC to replace FW with light brine (LB) as well as OB with gas blanket (GB). However, the expansion and control of cavern shape after replacement remains unclear, and it also needs to be clarified of the feasibility of SCC with LB. Therefore, the experimental and theoretical research on the physical simulation of SCC with LB under GB was carried out. Firstly, the dissolution test of salt rock in brine was performed, and the effect of brine concentration on the dissolution rate of salt rock was investigated, which provides foundation for the brine preparation of the physical simulation and on-site SCC. Then, based on dimensional analysis and similarity theory, a visual physical simulation platform of SCC under GB was established and five groups of physical simulation experiments were carried out. The effects of tube lifting method and circulation mode on the concentration of withdrawn brine and cavern shape were explored. The relationship between lateral dissolution angle and the effective volume of salt cavern energy storage were analyzed, and the measures and suggestions of controlling lateral dissolution angle and GB were proposed. Finally, the techno-economic analysis of SCC with FW and LB under GB was carried out, which shows that SCC with LB under GB possesses lower cost and better environmental protection. This research can serve as a basis for promoting clean and efficient brine mining and SCC. Highlights: The dissolution characteristics of typical salt rocks in China and abroad in different brine concentrations are explored. The effects of tube lifting and circulation mode on the concentration of produced brine and cavern shape are investigated. Measures and suggestions are put forward to regulate the salt cavern shape by controlling the gas blanket. Salt cavern construction with fresh water and light brine under gas blanket is compared and analysed.